Reinventando cotidianos de pesquisa - Gottardi, Denise Pesca Pereira (2010)
It aims to follow and question the movements of formation of research methods carried out by those who were studying for their Master’s or Doctorate’s degree in the Post Graduation Programs at the Universidade Federal do Espírito Santo (UFES) during 2008 and 2009. It seeks to follow the movements of production of research methods that are motioned in the daily tasks and that are produced among the impact of bodies that disturbs the researcher and forces him/her to think and create. Among these movements of creation and disarrangement of shapes and feelings – for what happens to the researcher and passes by him/her during the researches – it is important and necessary to evaluate the formation methods that we make work. In conclusion, it is this evaluation that questions the performance itself and that follows betting in a continuous creation of other methods, more powerful and life affirmative